RUMAH PINTAR MATAHARI SEBAGAI JENDELA ILMU BAGI ANAK JALANAN - Al Ubaidi, Jawahirul Ahmad; Pangestu, Hanif; Yuwafi, Ahmad Syukron (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2023)
This article describes the Matahari Smart House which has a secretariat building at SMP Muhammadiyah 11 Surabaya Jl. Dupak Bangunsari No. 50-54. This smart house was formed on February 14, 2013. On average, these street children follow their urbanized parents from villages to cities with the aim of changing their fate. However, their displacement is not equipped with qualified skills. So it is difficult for their families to survive in big cities, especially Surabaya. The method used to collect data in researching the institution is by observing, documenting, and interviewing resource persons from one of the founders of Rumah Pintar Matahari. This paper finds that Rumah Pintar Matahari persists in all situations, especially the COVID-19 pandemic, with the aim of providing moral and religious education to street children. Because they are concerned about the form of business street children are required to continue to learn while still looking for money for their lives. This paper concludes that Rumah Pintar Matahari comes with various approaches to children in the form of a persuasive approach, namely through affection and giving small gifts as appreciation for children who excel so that other children are more enthusiastic in learning.